ANALISIS YURIDIS PROGRAM PENDAFTARAN TANAH SISTEMATIS LENGKAP (PTSL) SEBAGAI UPAYA PEMBERANTASAN PRAKTIK MAFIA TANAH DI PEKANBARU - Muhammad Edra Alamsyah; Diding Rahmat (LEX OMNIBUS : Jurnal Hukum Tata Negara dan Administrasi Negara, 2024)
This research analyzes the juridical aspects of the Complete Systematic Land Registration Program (PTSL) in an effort to eradicate land mafia practices in Pekanbaru. PTSL is a government program that aims to speed up the land registration process in Indonesia, provide legal certainty, and reduce land disputes. This research uses a qualitative method with a normative juridical approach, involving literature study, analysis of statutory regulations. The research results show that the implementation of PTSL in Pekanbaru makes a positive contribution in suppressing land mafia practices through increasing transparency, data accuracy and legal certainty over land ownership. However, there are several challenges that need to be overcome, such as limited human resources, resistance from certain individuals, and technical obstacles in the land registration process. In conclusion, although PTSL is effective in minimizing land mafia practices, continued efforts are needed from the government and community to ensure the sustainability of this program and increase community legal awareness regarding land rights.